Pengembangan Model Pembelajaran Active Learning Jigsaw sebagai Optimalisasi Pembelajaran PAI di SMPN 3 Purwosari - Khofidatul Mukarromah; Askhabul Kirom; Saifulah; Ahcmad Yusuf (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The active learning jigsaw instructional model applied in this study is an adaptation of the traditional PAI (Islamic Religious Education) learning process. It is essential for teachers to adopt a clear model and approach to teaching effectively, as this significantly influences student learning outcomes. Teachers bear the responsibility for educational quality and thus require adequate capacity and knowledge. They should select appropriate teaching models tailored to the learning process. This research focuses on the interaction between educators and students during PAI instruction. Effective implementation of teaching models in the classroom can enhance student learning outcomes, such as through the active learning jigsaw method in PAI education. The study findings indicate positive and improved results from using the active learning jigsaw model, evidenced by increased classroom engagement, student discussions, and interactions with teachers. The researcher employed a qualitative research methodology, presenting descriptive findings using narrative rather than numerical data and statistics.